Comparison of two different techniques used for the maintenance of peri-implant soft tissue health: a pilot randomized clinical trial. (3rd October 2017) - Al Ghazal, Logien; O'Sullivan, Jeffery; Claffey, Noel; Polyzois, Ioannis
Abstract: Objectives: The aim of this pilot study was to compare the effectiveness of two different methods of debridement on maintaining and improving peri-implant soft tissue health over a period of 12 months. Materials and methods: Twenty adult patients (25 implants) were enrolled in a randomized, single-blinded, parallel group clinical trial. All implants included showed no signs of pathologic bone loss. Patients were scheduled to be reviewed every 3 months over a 12 months period. Nine patients (15 implants) were randomly allocated to a test group and treated with a low abrasive air polishing powder (Air-Flow ® Perio, EMS) (AFP) and another nine (10 implants) to a control group and treated with titanium curettes (TC). Peri-implant crevicular fluid samples were analyzed to quantitatively measure the concentration of six interleukins (IL-6, IL-8, IL-1β, TNF, IL-10 and IL-12). A multilevel analysis was used to test the comparison between the two treatments. The same analysis was used to study the relationship between clinical parameters and cytokines while controlling for confounding factors. Results: There was no significant difference in bleeding on probing (BOP) between the two treatment methods ( p  = .35). Both debridement techniques resulted in a similar reduction of BOP (40.04% and 39.93%). IL-6 was the only cytokine of the six investigated that demonstrated a correlation with a clinical parameter (BOP) ( p  = .05). Conclusions: Both treatment methods were proven to be effective in reducing peri-implant inflammation and preventing further disease progression. Some cytokines may act as markers for peri-implant disease as the present study showed a significant relationship between IL-6 and BOP.